INTEGRATION OF LEADERSHIP MANAGEMENT, EMOTIONAL INTELLIGENCE, AND THE EMOTIONAL INQUIRY LEARNING MODEL IN COMPETENCY-BASED TRAINING - Atiyah Suharti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This article discusses the conceptual link between leadership management, emotional intelligence, and the Emotional Inquiry learning model in the context of competency-based training. This study aims to examine how emotional intelligence is a crucial component in the effectiveness of leadership management, and how competency-based training that applies a reflective learning model can support leadership competency certification. The writing method uses a literature-based study approach by reviewing classical and contemporary scientific literature in the fields of leadership, emotional intelligence, and competency-based learning design. The results of the study indicate that effective leadership management requires not only intellectual intelligence and technical skills, but also high emotional intelligence to manage interpersonal relationships and strategic decision-making. Furthermore, competency-based training that adopts the Emotional Inquiry model can strengthen the reflective and affective dimensions of participants, so that the competency certification process more holistically reflects leadership capabilities. The implications of this study point to the need for integration between cognitive, affective, and socio-emotional aspects in the design of competency-based leadership training programs in Indonesia.